HUMAN CAPITAL AND ECONOMIC GROWTH IN SRI LANKA (Proceedings of The International Conference on Economics and Development, 2018)
Does a loss of skilled personnel in Sri Lanka reduce its potential for economic growth and development?  Talent shortage is a crisis for conflict driven countries and becomes a challenge to most post-conflict countries.  During the 30-year conflict, most Sri Lankans migrated due to political, economic, educational, social, cultural and environmental factors in search of security, stability and opportunity.  As a consequence of the war, Sri Lanka has scarce resources, a growing population, and a developing economy.  In order to promote peace and work towards sustainable development, it is vital for Sri Lanka to find creative ways to retain the best talent and also attract human capital.  A skilled workforce is one of the greatest assets for a post-conflict country during the development process.  Sri Lanka is gradually transitioning to become a knowledge-based economy; therefore, various sectors need to adapt to changing demands and provide practical solutions where necessary in order to reduce the skills gap and overcome any challenges hindering economic growth and sustainability.
Keywords: Human Capital; Talent; Knowledge-Based Economy